Pemilihan Supplier Jam Tangan Pada Toko Watchnineindo Menggunakan Metode Analytical Hierarchy Process - Ade Trisna Prasetiyo; Indro Kirono (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
Background - The rapid development of fashion is progressing quite rapidly, especially in the watch industry, watch shop entrepreneurs must be able to keep up with current developmentin the fashion world. In order to provide good quality watches, watch shop operators must have suppliers who are competitive overall. Aim - This study aims to select suppliers at the Watchnineindo watch shop based on five criteria, namely delivery, quality, service, price, and payment. Design / methodology / approach - This study uses an descriptive quantitative research method which has the aim of obtaining a complete picture of the views of the object under study from the data that has been processed and also to interpret clearly and detail onn decision making. The type of data uses primary data. Data collection techniques using a questionnaire. Findings - Based on the results of calculations using the Analytical Hierarchy Process (AHP) method, the criteria that received the highest weight were price with a weight of 0.446, second place was quality with a weight of 0.281, third place was payment with a weight of 0.130, fourth place were deliverywith a weight of 0.089, and the last is the service criteria with a weight of 0.055. While the sequence of suppliers that received the highest weight was Chinamontshopa with a weight of 0.286, the second was Antonj87 with a weight of 0.271, the third was CV.Indo jam with a weight of 0.166, the fourth was Arloji Watch Shop with a weight of 0.140, and the last one is The Time.ID with a weight of 0.137. Research implications - as a reference for further researchers related to the selection of suppliers for procurement of watch product. Limitations - For further researchers, more complete criteria can be used, namely using the 7P concept (product, location, place, promotion, people, process, physical evidence) because of the limitations of the researcher so that only 5 criteria are used in this study.